Health, healing and disease in South African township - Mills, Janet (Social Anthropology, 2025)
Intwaso is a condition which has been the subject of a great deal of psychological and psychiatric research over the past 50 years. Rarely have researchers rooted their interpretations within the social context, at either a micro or macro level. In this thesis it is argued that these omissions have resulted in a misunderstanding of the very nature· of the process of intwaso. This project therefore aims to both remedy and re-approach a study of the condition by locating it within a range of other illness-episodes suffered by household-members. Secondly, a particular illness, tuberculosis will be used as a control in order to establish the social determinants of differing patient-family prophylactic measures and therapy-management. This is of central importance to an understanding of intwaso as some social contexts create circumstances in which ancestral possession is the explanation for successive illnessepisodes and misfortunes. An understanding of the social recognition or non-recognition of intwaso, the initiation into and functioning of a diviner-school is also of importance to an understanding of the process of intwaso. The schools are seen as being shaped in response to the structural stresses of living in a South African township. The initial approach adopted in this thesis is to give a wide-angled "focusing shot" of the conditions and way of life of Guguletu residents, before honing in on a re-analysis of intwaso. The central tenet of this thesis is that without contextualization, a distorted interpretation of intwaso is inevitable, because the construction of the research design rules out the possibility of seeing the co-incidental nature of the condition.